1996
DOI: 10.3354/meps134059
|View full text |Cite
|
Sign up to set email alerts
|

Bioerosion and sediment ingestion by the Caribbean parrotfish Scarus vetula and Sparisoma viride:implications of fish size, feeding mode and habitat use

Abstract: Erosion rates and sources of sediment ingested were quantified for the 2 most abundant parrotfish species on a leeward fringing reef of Bonaire, Netherlands Antilles: Scarus vetula and Spansoma viride. Direct estimates of erosion by different size classes were obtained from daily feeding rates and grazing scar frequency, scar volume and substrate density. Foraging preference and distribution of fish on the reef were used to examine patterns of bioerosion at 2 spatial scales: reef zones and individual substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
2
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(190 citation statements)
references
References 17 publications
6
180
2
2
Order By: Relevance
“…trispinosus may be recognized as a scraper or excavator depending on its body size. All juvenile parrotfishes are scrapers (Bellwood & Choat, 1990), and their excavating potential may be related to body size (Bruggemann et al, 1996). We found that larger Sc.…”
Section: Discussionmentioning
confidence: 60%
“…trispinosus may be recognized as a scraper or excavator depending on its body size. All juvenile parrotfishes are scrapers (Bellwood & Choat, 1990), and their excavating potential may be related to body size (Bruggemann et al, 1996). We found that larger Sc.…”
Section: Discussionmentioning
confidence: 60%
“…The model was calibrated initially with demographic data of the stoplight parrotfish (Sparisoma viride) ( Fig. 1 A and B) from Bonaire in the early 1990s (22,23,24). Because fishing for parrotfish was absent at this time (20,23), and because the population of the stoplight parrotfish remained stable (25), we assumed that this dataset represents a relatively unfished demographic equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…S4). The resulting fishery model integrates the dynamics of the five dominant parrotfishes of Caribbean forereefs (29) that represent 80-95% of the total parrotfish abundance across the region (15,20,22,27). The impact of fishing was simulated with the demographic parameters as estimated for Bonaire populations, therefore assuming that total parrotfish biomass in Bonaire in the early 1990s [∌470 kg/ha (22)] constitutes a representative unfished biomass (B 0 ) for the Caribbean.…”
Section: Significancementioning
confidence: 99%
“…regrowth or accumulation, Brooks and Bell 2002). Since different substrata exhibit different physical characteristics, substratum composition is another factor that may influence the effects of a bioeroder (McLean 1967, Bruggemann et al 1996, Davidson et al 2008a.…”
Section: Factors Influencing the Effects Of Bioerodersmentioning
confidence: 99%
“…For example, McLean (1967) estimated the bioerosion rate of the snail Nerita tesselata was 0.7 g yr -1 , but total bioerosion from the high densities of this snail (220 m -2 ) exceeded 9000 cm 3 yr -1 of sandstone from a site in Barbados. Per capita rates of bioerosion can be affected by numerous factors such as the frequency of bioerosive action (Bruggemann et al 1996, Smith 2008), method of bioerosion (i.e. rasping, excavating, boring), and size of the bioeroder (McLean 1967, Bruggemann et al 1996, Carreiro-Silva and McClanahan 2001, Pinn et al 2005).…”
Section: Factors Influencing the Effects Of Bioerodersmentioning
confidence: 99%